APLIKASI PELABELAN BUKU DENGAN DECIMAL DEWEY CLASSIFICATION (DDC) PADA PERPUSTAKAAN TEKNIK INFORMATIKA UNIVERSITAS PALANGKA RAYA BERBASIS WEBSITE - Ronaldo, Deddy; Saputra, Aderay (JURNAL TEKNOLOGI INFORMASI, 2018)
The library is a building that contains a collection of books and other archivesin physical form neatly arranged in the building room, easy to find and use when neededby the reader.DDC (Decimal Dewey Classification) is the most widely used classificationsystem in the world. DDC is used to manage and provide access to a collection of booksin the library. The DDC is divided into ten main classes, which together cover the entireworld of knowledge. Consisting of ten main classes, one hundred divisions, and onethousand parts.Various problems found in the system are still manual, for example labeling andcategorizing books that are not suitable, therefore the authors chose this title to beappointed in the Practical Work College proposal because the author wanted to improvethe library work system, especially the Informatics Engineering Library of PalangkarayaUniversity. This application aims to improve the efficiency of library work. This libraryapplication was built using the PHP language (Hypertext Prepocessor). Dengandidukung oleh perangkat lunak seperti Net Beans, Photoshop dan XAMPP.